2020
DOI: 10.3390/horticulturae6040086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Crop Water Stress Index as an Indicator for the Diagnosis of Grapevine Water Deficiency in Greenhouses

Abstract: Precise irrigation management of grapevines in greenhouses requires a reliable method to easily quantify and monitor the grapevine water status to enable effective manipulation of the water stress of the plants. This study evaluated the applicability of crop water stress index (CWSI) based on the leaf temperature for diagnosing the grapevine water status. The experiment was conducted at Yuhe Farm (northwest China), with drip-irrigated grapevines under three irrigation treatments. Meteorological factors, soil m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 57 publications
4
33
0
1
Order By: Relevance
“…In the V (Figure 4A), R (Figure 4B), and M stages (Figure 4C) of maize growth, there were no significant differences in the NWSB slopes of ZD958 and XY335. Because the NWSB slope reflects crop transpiration capacity, this indicated that the transpiration rates of ZD958 and XY335 were similar in each growth stage [50]. However, there were significant differences in the NWSB intercept between genotypes in each growth stage.…”
Section: Significant Differences In Nwsb Are Attributed To the Differ...mentioning
confidence: 95%
“…In the V (Figure 4A), R (Figure 4B), and M stages (Figure 4C) of maize growth, there were no significant differences in the NWSB slopes of ZD958 and XY335. Because the NWSB slope reflects crop transpiration capacity, this indicated that the transpiration rates of ZD958 and XY335 were similar in each growth stage [50]. However, there were significant differences in the NWSB intercept between genotypes in each growth stage.…”
Section: Significant Differences In Nwsb Are Attributed To the Differ...mentioning
confidence: 95%
“…Although we cannot guarantee that every measurement was taken on a sunny and windless day, the data were averaged on a large number of measured values (270 data every time), which help to minimize the discrepancy in data and the adverse effect of weather factors. As an index indicating the severity of drought stress on plants, CWSI was adopted and defined as [43]:…”
Section: Crop Water Stress Indexmentioning
confidence: 99%
“…The upper limit was the soil field capacity, and the lower limit was 65% of the upper limit during the shoot growth stage and the veraison and maturity stages and 70% of the upper limit during the fruit expansion stage. The calculation formula for M [31] is expressed as follows:…”
Section: Experimental Designmentioning
confidence: 99%